2020
DOI: 10.1038/s41419-020-2635-5
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circSLC25A16 contributes to the glycolysis of non-small-cell lung cancer through epigenetic modification

Abstract: Growing evidence has highlighted the roles of circular RNAs (circRNAs) in non-small-cell lung cancer (NSCLC), however, their roles in NSCLC glycolysis remains poorly understood. CircRNAs microarray profiles discovered a novel exon-derived circRNA, circSLC25A16 (hsa_circ_0018534), in NSCLC tissue samples. In NSCLC samples, high-expression of circSLC25A16 was associated with unfavorable prognosis. Cellular experiments revealed that circSLC25A16 accelerated the glycolysis and proliferation of NSCLC cells. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…Certain circRNAs have been demonstrated to exert roles in human cancers, serving as cancer-promoting or cancer-suppressing factors [ 5 , 6 ]. Many circRNAs were reported to affect NSCLC progression, like circSLC25A16, hsa_circ_0043265, circRNA_001010 and hsa_circ_0072309 [ 7 10 ]. Back-spliced from aldehyde dehydrogenase 4 family member A1 (ALDH4A1), circRNA hsa_circ_0010235 (Position: chr1:19201875–19216599) was detected to be upregulated in NSCLC tissues [ 11 ], while its explicit role in NSCLC development remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Certain circRNAs have been demonstrated to exert roles in human cancers, serving as cancer-promoting or cancer-suppressing factors [ 5 , 6 ]. Many circRNAs were reported to affect NSCLC progression, like circSLC25A16, hsa_circ_0043265, circRNA_001010 and hsa_circ_0072309 [ 7 10 ]. Back-spliced from aldehyde dehydrogenase 4 family member A1 (ALDH4A1), circRNA hsa_circ_0010235 (Position: chr1:19201875–19216599) was detected to be upregulated in NSCLC tissues [ 11 ], while its explicit role in NSCLC development remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, circTLK1 positively regulated the expression of CBX4 by sponging miR-136-5p [29]. Additionally, circSLC25A16 functioned as a miR-488-3p sponge to suppress HIF-1α [30]. In this paper, we identi ed PDCD10 as a potential candidate gene of miR-1270 using online bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 98%
“…CircSLC25A16 interacts with miR-488-3p/HIF-1α and activates LDHA by facilitating its transcription. 22 In addition, it was reported that the downregulation of serine/arginine splicing factor 1 (SRSF1) contributed to, at least in part, the increased expression of circSETD3 in NSCLC cells with acquired resistance to gefitinib in NSCLC. 23 Research has confirmed that the present research performed a circRNA microarray analysis for the expression profile and identified a novel circRNA (circMAGI3, hsa_circ_0110498).…”
Section: Discussionmentioning
confidence: 99%